PERCEIVED INFLUENCE OF MEMORIZATION AND SELF INSTRUCTIONAL LEARNING STRATEGIES ON PRIMARY SCHOOL PUPILS ACADEMIC PERFORMANCE IN ENGISH STUDIES IN IDEMILI NORTH LGA, ANAMBRA STATE - Ikebuaso, Royaline Amarachi; Obumneke-Okeke, Ifeoma Mabel (Journal of Early Childhood and Primary Education, 2020)
The study was designed to determine the perceived influence of memorization and self-instructional learning strategies on primary school pupilsâ€™ academic performance in English studies in Idemili North Local Government Area of Anambra State. Two research questions guided the study. Descriptive survey research design was adopted. The population of the study comprised of 428 primary school teachers in 70 public primary schools in Idemili North Local Government Area of Anambra State. Simple random sampling technique was used to select a sample of 80 primary school teachers from 10 public primary schools out of the 70 public primary schools. The researcher developed a questionnaire titled â€œPerceived Influence of Memorization and Self-Instructional Learning Strategy on Pupils Academic Performance (PIMSLS-PAP)â€. The instrument was validated by three experts two from Department of Early Childhood and Primary education and one from Measurement and Evaluation, Department of Educational Foundations all from the Faculty of Education, Nnamdi Azikiwe University, Awka. Cronbach alpha was used to test the reliability of the instrument and reliability coefficient of 0.83 and 0.76 was obtained with an overall reliability coefficient of 0.80 was obtained. Mean and standard deviation were used to analyze the data collected. Findings of the study revealed that primary school teachers agreed that memorization strategy enhances the reading culture of pupils, reduces tensions among pupilsâ€™ when studying English studies and is easy and quick for teaching pupils among others. The study disclosed that primary school teachers perceived that self-instructional strategy improves pupilsâ€™ reading, speaking, writing and pronunciation skills among others. It was recommended among others that English studies teachers in primary school should create an atmosphere that is conducive for pupils to memorize and use self instructional learning strategy in order to instil reading culture and improve their proficiency in English studies.